Associations between common polymorphisms in CYP2R1 and GC, Vitamin D intake and risk of colorectal cancer in a prospective case-cohort study in Danes - Kopp, Tine Iskov (PLoS One, 2020)
BACKGROUND: The association between vitamin D and incidence of colorectal cancer has been thoroughly investigated, but the results are conflicting. The objectives in this study were to investigate whether two functional polymorphisms in GC and CYP2R1, respectively, previously shown to predict vitamin D concentrations, were associated with risk of colorectal cancer; and further, to assess gene-environment interaction between the polymorphisms and intake of vitamin D through diet and supplementation in relation to risk of colorectal cancer. METHODS: A nested case-cohort study of 920 colorectal cancer cases and 1743 randomly selected participants from the Danish prospective “Diet, Cancer and Health” study was performed. Genotypes CYP2R1/rs10741657 and GC/rs4588 were determined by PCR-based KASP(™) genotyping assay. Vitamin D intake from supplements and diet was assessed from a validated food frequency questionnaire. Incidence rate ratios were estimated by the Cox proportional hazards model, and interactions between polymorphisms in GC and CYP2R1 and vitamin D intake in relation to risk of colorectal cancer were assessed. RESULTS: Neither of the two polymorphisms was associated with risk of colorectal cancer per se. Heterozygote carriage of CYP2R1/rs10741657 and GC/rs4588, and carriage of two risk alleles (estimated by a genetic risk score) were weakly associated with 9–12% decreased risk of colorectal cancer per 3 μg intake of vitamin D per day (IRR(CYP2R1/rs10741657) = 0.88, 95% CI: 0.79–0.97; IRR(GC/rs4588) = 0.91, 95% CI: 0.82–1.01, IRR(GRS2) = 0.90, 95% CI: 0.81–0.99). CONCLUSIONS: The results suggest that genetic variation in vitamin D metabolising genes may influence the association between vitamin D intake, through food and supplementation, and risk of colorectal cancer. CLINICAL TRIAL REGISTRY: NCT03370432. Registered 12 December 2017 (retrospectively registered).